Hydrothermal Production of H2 and Magnetite From Steel Slags: A Geo-Inspired Approach Based on Olivine Serpentinization - Brunet, Fabrice (Frontiers in Earth Science, 2019)
The interaction between ultramafic rocks and hot seawater at slow-spreading mid-oceanic ridges triggers hydrothermal redox reactions which are known to produce magnetite and H2 under appropriate pressure and temperature conditions. Steel slags share some common properties with ultramafic rocks. They are composed of anhydrous and refractory minerals formed at temperatures exceeding 1,200°C and they contain ferrous iron in comparable amounts. Consequently, when submitted to hydrothermal conditions both types of materials, natural and anthropogenic, are prone to form magnetite and H2 according to the simplified redox reaction: 3[FeO] + H2O = > Fe3O4 + H2 (1) where [FeO] is the ferrous iron component of the corresponding material that can be present under different mineralogical forms. Since H2 and magnetite are two valuable products for applications in new technologies, the hydrothermal treatment of steel slags can be seen as a way to valorize a byproduct of the steel industry, a few tenths of a billion tons of which are produced yearly. The hydrothermal behavior of steel slags which arise from basic oxygen furnace (BOF) operations and that of olivine (Mg,Fe)2SiO4, the main mineral constituent of abyssal peridotites, are described here based on data from the literature. The thermochemical characteristics of Reaction 1 are reviewed for both types of materials in the perspective of optimizing a process that would valorize BOF steel slags for the production of nanomagnetite (and high-purity H2). In particular, the kinetics effect of temperature, pH and solution-to-solid mass ratio on the hydrothermal oxidation of wüstite (FeO), considered here as an analog of the ferrous-iron component of steel slags, are modeled. The possible role of additives (impurity) on the hydrothermal oxidation of wüstite through the catalysis of the water-splitting reaction is discussed. Finally, the lack of kinetics constraints on nanomagnetite growth under hydrothermal conditions in a wide range of pH is identified as a major gap in the understanding of two important issues: (1) the catalysis of abiotic molecules in the course of serpentinization reactions, and (2) the tailoring of the size of the magnetite produced by hydrothermal treatment of BOF steel slags.